Pendampingan Penyusunan Pembelajaran Berdiferensiasi Kurikulum Merdeka bagi Guru Kimia MGMP Kota Semarang - Haryani, Sri; Wardani, Sri; Tri Prasetya, Agung; Susilaningsih, Endang; Budi Susatya, Eko; Herlina Dewi, Siti (Penerbit Goodwood, 2024)
Purpose: Implementation of the Merdeka Curriculum in Indonesia in 2020 has not been effective or optimal. Most teachers are still trying to adapt, and some still have difficulty implementing learning with the Merdeka Curriculum and differentiated learning. The purpose of this service activity was to improve teachers' understanding and skills in implementing differentiated learning. Methodology: This community activity program was conducted through assistance consisting of lectures, discussions, and workshops. The success of the activity can be seen in the assessment of learning tools and the filling out of questionnaires. Results: Based on the results of problem identification, this service activity aims to improve the ability of differentiated learning design and the availability of various sample devices for different chemical materials. The activities included: (1) deepening of chemical literature through lectures and discussions, (2) seminars on analyzing CP, TP, and ATP, (3) seminars on preparing different learning needs, and (4) workshops on preparing learning modules. Limitations: The number of participants in the service program was limited. The participants came from MGMP Kimia Semarang for approximately 30 people. The results may be different for other participants. Contribution: Improving the knowledge and skills of chemistry teachers in Semarang City to design differentiated learning for the Merdeka Curriculum.